The Goat Lady - Bregoli, Jane, 1952- (Gardiner, Me. : Tilbury House, 2004)
Tells the story of an elderly French-Canadian woman who lived in Massachusetts and raised goats to provide milk for people who needed it.
Accelerated Reader AR
Maine Student Book Award list, 2005-2006
Keywords: Houle, Noelie Lemire, -- b. 1899 -- Juvenile literature; Houle, Noelie Lemire, -- b. 1899.; Goat farmers -- Massachusetts -- Dartmouth -- Biography -- Juvenile literature; Goats; Old age; Dartmouth (Mass.) -- Biography -- Juvenile literature